Relationship of ventricular and atrial dilatation to valvular function in endurance athletes - Prakken, N. H.; Velthuis, B. K.; Bosker, A. C.; Mosterd, A.; Teske, A. J.; Mali, W. P.; Cramer, M. J. (British Journal of Sports Medicine, 2011)
Objective To establish cardiac magnetic resonance imaging (MRI) reference values for atrial adaptation to training in endurance athletes in comparison with matched non-athletes. In addition, to study the relationship of atrial size to ventricular and annular size and valvular function.